2017
DOI: 10.14260/jemds/2017/1107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stump Closure Techniques of the Base of the Appendix in Laparoscopic Appendectomy

Abstract: BACKGROUNDAppendicitis remains one of the most common surgical diseases. Open or laparoscopic appendectomy remains the gold standard treatment for acute appendicitis. The technique of appendectomy may vary from surgeon to surgeon or from centre to centre, starting from skin incision to ligation and invagination of appendiceal stump. However, concerns still exist regarding appendiceal stump closure.The present study was conducted to compare the stump closure techniques of Endoloop versus Intracorporeal Transfix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our result is similar to Chand Prem et al, 2017, who reported in their study comparing Intracorpor-eal knot with endoloop that the mean age of all patients was 29.01 years, and they explained the cause of high incidence of appendicitis in the second and third decade of life is considerably due to hyperplasia of lymphoid tissue in the appendix, which reaches its peak at 20 years of age and thereafter atrophy of the lymphoid tissue begins [9] . Nadeem et al, 2016 reported in their study comparing Endoloop (sliding knot) that (36 patients) with metallic endoclip (32 patients), that the mean age of Endoloop group was 24 ±7.78 years [10] .…”
Section: Commercial Endoloops Use the Knot Which Hanssupporting
confidence: 92%
See 1 more Smart Citation
“…Our result is similar to Chand Prem et al, 2017, who reported in their study comparing Intracorpor-eal knot with endoloop that the mean age of all patients was 29.01 years, and they explained the cause of high incidence of appendicitis in the second and third decade of life is considerably due to hyperplasia of lymphoid tissue in the appendix, which reaches its peak at 20 years of age and thereafter atrophy of the lymphoid tissue begins [9] . Nadeem et al, 2016 reported in their study comparing Endoloop (sliding knot) that (36 patients) with metallic endoclip (32 patients), that the mean age of Endoloop group was 24 ±7.78 years [10] .…”
Section: Commercial Endoloops Use the Knot Which Hanssupporting
confidence: 92%
“…Time was significantly longer because invaginating suture was also used in the study [14] . Chand, Prem, et al, 2017, reported in their study on 60 patients that the bowel sounds in patients of sliding knot group (30 patients) returned after 18.80 ±8.14 hours [9] . Regarding postoperative complications: Only one patient (5.0%) in group (I) developed superficial wound infection, while two patients (10.0%) in group (II) had wound infection and regarding intra-abdominal abscess there was one patient only in group (II) that has postoperative abscess in the right iliac fossa (5.0%),only one patient in group (I) (5.0%) developed port site hernia at 3 rd month and one patient in group (II) (5.0%) developed adhesions (adhesive intestinal obstruction) at 6 th month.…”
Section: Commercial Endoloops Use the Knot Which Hansmentioning
confidence: 93%
“…19,20 Closure with endoloop is commonly done due to its lower cost compared to stapler. 21 The use of endoloop is less expensive but needs trained surgeon and stapler is safe and fast but expensive. The disadvantage of clips being spilled into abdominal cavity may cause peritoneal adhesion and intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%